Expression of microRNA-379 reduces metastatic spread of prostate cancer - Cassidy, James R.; Voss, Gjendine; Underbjerg, Kira Rosenkilde; Persson, Margareta; Ceder, Yvonne (Frontiers in Oncology, 2023)
Prostate cancer (PCa) is the most common type of cancer in males, and the metastatic form is a leading cause of death worldwide. There are currently no curative treatments for this subset of patients. To decrease the mortality of this disease, greater focus must be placed on developing therapeutics to reduce metastatic spread. We focus on dissemination to the bone since this is both the most common site of metastatic spread and associated with extreme pain and discomfort for patients. Our strategy is to exploit microRNAs (miRNAs) to disrupt the spread of primary PCa to the bone. PCa cell lines were transduced to overexpress microRNA-379 (miR-379), which was assessed using in vitro and in vivo functional assays. PCa cells with increased levels of miR-379 showed a significant decrease in proliferation, migration, colony formation, and adhesion to bone cells in vitro. A potential mechanism is unravelled whereby miR-379 deregulation in PCa cells affects the secretion of GDF-15 from osteoblasts which in turn facilitates the metastatic establishment in bone. In vivo miR-379 overexpression in PC3 cells significantly decreased metastatic spread to bone, and reduced levels of miR-379 were seen in PCa patients with metastases. Taken together, this supports the potential role of miR-379 as a therapeutic solution for prostate cancer.